Short Communication Diagnosis and Efficacy of Brucella abortus Strain RB51 in Experimentally Inoculated Sprague - Dawley Rats Using Dot Blot Assay (Biological Sciences - PJSIR, 2007)
Sprague-Dawley  (SD)  rats  were  experi mental l y  i nocu lated  wi th  Bruce/la  abortus  strain  R l35 I  and  challenged 4 weeks post i nocul ation w ith B. abortus bi otype  I . Mon itori ng of the  sera  by  dot-blot  assay  and  cl i n ical  exam i nation  of the rats revealed  the h ighest i m m une response. SR B5 I   was isolated  from the blood  of all  i nocu l ated  rats u nti l   !"week  post    i noculation wi thout any cl i nical sign. f t is concl uded th at SR B5 I produces i mm u n i ty  i n  SD rats and  i nduces  protection against  B.  abortus  biotype   I   and  that  Dot  Blot  Assay  is  an  easy,  less  time  consumi ng  and  correct-resul t  readi ng test.